Fabrication of cerium doped carbon dots with highly radical scavenging activity alleviates ferroptosis-induced oxidative damage. (9th July 2021) - Cai, Rong; Xiao, Long; Qiu, Jianghong; Zhao, Lulu; Li, Zhuoxin; Ju, Huixiang; Sun, Mingzhong; Zhu, Wenkai; Wang, Zhirong; Du, Fengyi
Abstract: Ferroptosis as an iron-dependent lipid peroxidation process causes sevely oxidative damage of cell, but lack of highly efficient and recycable antioxidant agents. To this end, cerium doped carbon dots (Ce-doped CDs) with radical scavenging activity were synthesized using a simple microwave-assisted hydrothermal carbonization. The resultant Ce-doped CDs exhibited an ultra-small size of only approximately 2.6 nm, excellent dispersion in water as well as optical performance. Taking advantage of inherent ultra-small size, Ce-doped CDs were endowed with high Ce 3+ /Ce 4+ ratio, which significantly enhanced their radical scavenging activity. Meanwhile, the Ce-doped CDs with superior biocompatibility could enter cells quickly and then localized in the cytoplasm. As we expected, the Ce-doped CDs strongly protected cells from oxidative damage of erastin-mediated ferroptosis. These findings suggest that the as-prepared Ce-doped CDs have the potential to be antioxidant drugs against for ferroptosis-induced oxidative damage.